INFLUENCE OF TRACE METALS ON STRUCTURAL AND FUNCTIONAL CHARACTERISTICS OF CANCELLOUS BONE IN 21 DAYS OF REPARATIVE OSTEOGENESIS - Гусак, Є.В. (World of Medicine and Biology, 2016)
The research presents the results of influence trace metals on structural and functional characteristics of cancellous bone on day 21 reparative osteogenesis. In the course of the study we used the methods of X ray diffraction and impact toughness. Analysis of microstructural parameters indicated that the crystallites were generally smaller and the lattice microstrain level was higher in the experimental group than at the baseline. The use of the impact toughness method as energy characteristics of cancellous bone demonstrated the level decreases of resistance to brittle fracture of more than two in the experimental group. The results of the study show the negative impact of trace metals on regenerative capacity of cancellous bone. Changing parameters of the mineral microstructure and sacrifice in mechanical properties have been found.
Keywords: cancellous bone; reparative osteogenesis; X-ray diffraction; impact toughness; mechanical properties